Analysis of Consistency and Quality of Planning and Budgeting in Infrastructure Development in the Solok City Regional Government - Citra Dewi Ramlia; Suhanda (Badan Penerbit STIEPARI Press, 2025)
This study examines the consistency and quality of infrastructure planning and budgeting within Solok City's local government in Indonesia, particularly focusing on the Department of Public Works and Spatial Planning (DPUPR) and the Department of Housing and Settlement Areas (Diperkim). The research highlights the challenges in aligning strategic planning documents, such as the RPJMD 2021–2026, with annual implementation frameworks, including RKPD, KUA-PPAS, and APBD. These challenges were intensified by institutional restructuring and fiscal limitations. The research employs a descriptive case study methodology (Yin, 2009), utilizing primary data collected from structured interviews with 11 key government officials. Secondary data included relevant planning and budgeting documents from 2021–2025. To measure consistency, the Planning and Budgeting Consolidation Matrix (MKPP) was used, while quality was assessed based on Baer's (1997) criteria and the SAKIP performance indicators. The findings reveal that initial inconsistencies were evident between 2021 and 2022, largely due to the transfer of water and sanitation programs from Diperkim to DPUPR under Ministerial Decree No. 050-5889/2021. This caused misalignments between the RPJMD targets and the budgetary execution. However, by 2023–2025, the integration of the SIPD digital system and the standardization of nomenclatures led to full consistency (100%). Moreover, the quality of infrastructure planning and budgeting improved from